Compound‐specific 15N analysis of amino acids: A tool to estimate the trophic position of tropical seabirds in the South China Sea. Issue 17 (11th August 2018) - Wu, Libin; Liu, Xiaodong; Xu, Liqiang; Li, Linjie; Fu, Pingqing
Abstract: Compound‐specific 15 N analysis of amino acids (AAs) is a powerful tool to determine the trophic position (TP) of organisms. However, it has only been used in a few studies of avian ecology because the AA patterns in the consumer‐diet nitrogen trophic discrimination factor (TDFG lu‐Phe = ∆ 15 NG lu −∆ 15 NP he ) were unknown in birds until recently, and tropical seabirds have never been investigated with this methodology. Here, we explore the application of this method to tropical seabirds. In this study, we recovered the fossilized bones of tropical seabirds from ornithogenic sediments on two coral islands in the Xisha Islands, South China Sea, as well as the bones and muscle of their predominant food source, flying fish ( Exocoetus volitans ). Compound‐specific 15 N and 13 C analyses of AAs in both seabird and fish bone collagen were conducted. The TP of flying fish was calculated based on a widely used single TDFG lu‐Phe approach. We then calculated the TP of tropical seabirds in three different ways: (a) according to the composition of their diet; (b) based on the single TDFG lu‐Phe approach; and (c) using a multi‐TDFG lu‐Phe approach. The results of the multi‐TDFG lu‐Phe approach were much closer to the results based on the composition of the seabird diet than the results of the single TDFG lu‐Phe approach, confirming its applicability for tropical seabirds. For seabird bone samples of different ages, TP determined from the multi‐TDFG lu‐Phe approach was most similar to that of bulk δ 15 N of bird collagen, with seabirds occupying higher TPs during the Little Ice Age, as previously shown. In addition, the 13 C Suess effect was reflected in the AAs δ 13 C in our samples. This study applied a compound‐specific 15 N analysis of AAs to determine the TP of tropical seabirds that has potential to extend to all tropical seabirds many of which are widely distributed and play a key role in the evolution of coral island ecosystems. Abstract : This study applies compound‐specific 15N analysis of amino acids to determine trophic position of tropical seabirds and has extensive applications due to the key role of tropical seabirds in the evolution of coral island ecosystems.